1978
DOI: 10.1177/014662167800200413
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Psychometric Rating Model to Ordered Categories Which Are Scored with Successive Integers

Abstract: A latent trait measurement model in which ordered response categories are both parameterized and scored with successive integers is investigated and applied to a summated rating or Likert ques tionnaire. In addition to each category, each item of the questionnaire and each subject are para meterized in the model; and maximum likelihood estimates for these parameters are derived. Among the features of the model which make it attractive for applications to Likert questionnaires is that the total score is a suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
178
0
11

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(189 citation statements)
references
References 8 publications
0
178
0
11
Order By: Relevance
“…Measurement models based on item response theory also include models that are applicable to personality instruments that are not dichotomously scored (24)(25)(26)(27)(28). In terms of psychiatric measurement, research has demonstrated that both item response theory and CAT (29) can be meaningfully applied to the measurement of attitudes and personality variables (30,31).…”
mentioning
confidence: 99%
“…Measurement models based on item response theory also include models that are applicable to personality instruments that are not dichotomously scored (24)(25)(26)(27)(28). In terms of psychiatric measurement, research has demonstrated that both item response theory and CAT (29) can be meaningfully applied to the measurement of attitudes and personality variables (30,31).…”
mentioning
confidence: 99%
“…The construct validity of the SPEF-R was examined using the RMM, specifically in the three aspects: (1) rating scale analysis, (2) test unidimensionality, and (3) test targeting. The Rasch Rating Scale model (Andrich, 1978) was used in this study because the 5-point rating scale of the SPEF-R represents use of the same rating criteria across individual items. The RMM analysis was performed using the WINSTEPS computer software version 3.73 (Linacre, 2011), and details of each part are described below.…”
Section: Resultsmentioning
confidence: 99%
“…Measurement reliability was estimated with both classical and Rasch analyses. Using latent trait modeling, item response data was fitted to the Rasch unidimensional rating scale measurement model (Andrich, 1978). In addition to estimating item rating scale model parameters, we tested the assumption that the item response process was unidimensional.…”
Section: Methodsmentioning
confidence: 99%